Remote Sensing in the Management of Rangelands - Tueller, Paul T (Annals of Arid Zone, 2016)
Remote sensing technology is rapidly maturing. Applications for range management continue to develop and are dependent upon three requirements: (1) continued remote sensing technology development; (2) application scientists and managers with optimum knowledge of the rangeland ecosystems to be managed; and (3) a continuing improvement in the arid land rangeland knowledge base consisting of information on vegetation, soils, climate, water, fauna, etc . for the area to be managed and monitored. In addition, the rapidly developing computer infrastructure and the significant potential contributions of Geogrdphic Information Systems, Global Positioning Systems now place remote sensing in a premier place among the possible techniques or new science available to assist range managers in their work.